The complete mitochondrial genome of Argiope ocula (Araneae: Araneidae) and its phylogeny - Yan, Yi (Mitochondrial DNA B Resour, 2019)
The complete mitochondrial genome of Argiope ocula (GenBank accession number MN331657) is a circular molecule of 14,079 bp in length, comprising of 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), two ribosomal RNA genes, and a control region. Ten intergenic spacer regions and 19 reading frame overlaps were found in the mitogenome of A. ocula. Ten tRNAs (trnD, trnF, trnK, trnR, trnT, trnW, trnE, trnG, trnL(1), and trnM) lacked the TΨC arm stem, whereas three tRNAs (trnA, trnS(1), and trnS(2)) lost the dihydrouracil (DHU) arm. Phylogenetic analysis suggested that A. ocula had the closest evolutionary relationship with A. perforata.